2022
DOI: 10.3390/ijerph191912083
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Virtual-Reality-Based Restorative Environments on Creativity

Abstract: This study, based on the theory of complex therapeutic environments, uses virtual reality (VR) technology to construct interactive restorative environments and discusses the influence of the experience of virtual restorative environment on individual creativity. A total of 72 college students were selected as participants in the study. Through psychological scales, three creativity tests, and EEG feedback data, the following conclusions were drawn:(1) The VR restorative environment experience improves individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 115 publications
0
1
0
Order By: Relevance
“…G-Tec [9] ASA Lab, ANT [51,68] Nihon Kohden [39] LiveAmp [10,44] g.LADYBIRD [11,12,50] g.GAMMAsys [72] g.USBamp [36] g.tec Nautilus [82] Brain Products [77] QuickAmp [79] actiCHamp [62,63] BrainAmp [46] BrainAmp Move System [54,76] Enobio 3 [13] Enobio-32 [88] StarStim 8 [35] EPOC Flex [14] Neuracle [17,18] OpenBCI [47][48][49] Biosemi Active Two [21] Biosemi Actiview [42,43] V-Amp [22] ANT Neuro [52,53,64] eegoSports [81] ActiCAP [25,28,57,67,70,78] BIOPAC MP160 [75] Mobita [83] EasyCap [32,41,85,86] Scan SynAmps2 Express [30] Cur...…”
Section: Eeg Equipmentmentioning
confidence: 99%
See 3 more Smart Citations
“…G-Tec [9] ASA Lab, ANT [51,68] Nihon Kohden [39] LiveAmp [10,44] g.LADYBIRD [11,12,50] g.GAMMAsys [72] g.USBamp [36] g.tec Nautilus [82] Brain Products [77] QuickAmp [79] actiCHamp [62,63] BrainAmp [46] BrainAmp Move System [54,76] Enobio 3 [13] Enobio-32 [88] StarStim 8 [35] EPOC Flex [14] Neuracle [17,18] OpenBCI [47][48][49] Biosemi Active Two [21] Biosemi Actiview [42,43] V-Amp [22] ANT Neuro [52,53,64] eegoSports [81] ActiCAP [25,28,57,67,70,78] BIOPAC MP160 [75] Mobita [83] EasyCap [32,41,85,86] Scan SynAmps2 Express [30] Cur...…”
Section: Eeg Equipmentmentioning
confidence: 99%
“…The authors of [57] showed that goal directed attention may be assessed, using a saccadic eye experiment, where brain activity was evaluated through EEG analysis. The effects of restorative VEs on subject' attention and engagement for three creativity tests were assessed in study [75]. An increase in attention and engagement levels was associated with improvements on subjects' creativity.…”
Section: Objectives and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental psychology research showed that built environments with natural elements were more popular and more positively evaluated by people ( Ulrich, 1983 ; Brandt and Shook, 2005 ). Attention Recovery Theory ( Kaplan and Kaplan, 1989 ) and Psychological Recovery Theory (also known as Stress Reduction Theory, Ulrich, 1991 ) posit that introducing natural elements into the built environment can effectively help people recover from psychological depletion and improve their psychological wellbeing more generally ( Burnard et al, 2017 ; Li et al, 2022 ). Specifically, Attention Recovery Theory states that natural views provide stimulation which activates undirected attention and restores depleted attention system ( Kaplan and Kaplan, 1989 ; Kaplan, 1995 ), while Stress Reduction Theory believed that natural environments could aid recovery from stressful events, block negative thoughts, and turn emotions to positive side, help people restore healthy cognition and behavior ( Ulrich, 1983 ; Ulrich, 1991 ; Ulrich et al, 1991 ).…”
Section: Introductionmentioning
confidence: 99%